Minimally invasive, iliac crest-sparing approach for pelvic osteotomies in children. Issue 4 (July 2017) - Ghanem, Ismat; Sebaaly, Amer; Pedro, Nakhle; Saliba, Elie
Abstract : The aim of this article is to describe a minimally invasive iliac crest-sparing approach (ICSA) allowing common iliac osteotomies in children. The ICSA was used for 98 hips in 72 consecutive patients who underwent a pelvic osteotomy. The mean follow-up duration ranged from 3 to 7 years. Skin incision ranged from 3 to 5.5 cm. Displacement of the distal osteotomy fragment was easy and without tension. The duration of surgery varied from 50 min in the beginning of our experience to 20–25 min for the last cases of the series. In conclusion, the ICSA fulfills all the criteria of minimally invasive surgery.